An Assessment of the Efficacy of Pheromone Traps in Managing the Red Palm Weevil - Rachid Sabbahi; Khalil Azzaoui; Belkheir Hammouti (Indonesian Journal of Science and Technology, 2021)
This experiment was performed in date palm farms to assess the effectiveness of a newly designed pheromone trap (i.e., funnel trap) in capturing red palm weevil (RPW) adults and to compare it to traditional traps. The number of captured RPWs varied by month, with a total of 3931 adults captured during the experiment. Analysis of variance demonstrated significant differences in the number of captures between the three traps. The funnel traps captured 1627 RPW adults in total, while the buried and burlap bucket traps captured 1079 and 1225 weevils, respectively. The mean (± SE) number of captures/trap/weeks was 2.62 ± 0.11 in funnel traps, which was significantly higher than that of buried bucket traps (1.73 ± 0.06) and burlap bucket traps (1.97 ± 0.07). Both sexes were attracted to traps; however, the number of female weevils captured was significantly higher than that of males with a sex ratio (female/male) of 1.58 ± 0.03. According to the findings, the pheromone-food-bait funnel trap is a promising solution for reducing RPW populations and thus protecting date palm trees from infestations.